Through a Glass, Darkly: Tactical Support and Symbolic Association in Twitter Messages Commenting on Stuttgart 21. (February 2014) - Jungherr, Andreas; Jürgens, Pascal
Political actors increasingly use the microblogging service, Twitter, for the organization, coordination, and documentation of collective action. These interactions with Twitter leave digital artifacts that can be analyzed. In this article, we look at Twitter messages commenting on one of the most contentious protests in Germany's recent history, the protests against the infrastructure project Stuttgart 21. We analyze all messages containing the hashtag #s21 that were posted between May 25, 2010, and November 14, 2010, by the 80, 000 most followed Twitter users in Germany. We do this to answer three questions: First, what distinguishes events that resulted in high activity on Twitter from events that did not? Second, during times of high activity, does the behavior of Twitter users vary from their usual behavior patterns? Third, were the artifacts (retweets, links) that dominated conversations during times of high activity indicative of tactical support of the protests or of symbolic association with it?